A comunidade zooplanctônica em lagoas de uma planície de inundação neotropical : estrutura e papel funcional. - Dias, Juliana Déo (Universidade Estadual de Maringá. Departamento de Biologia. Programa de Pós-Graduação em Ecologia de Ambientes Aquáticos Continentais., 2012)
A major advance for studies in community ecology is to unravel the role played by communities in ecosystem processes and the environmental mechanisms that rule these processes. Among ecosystem processes, highlights the zooplankton secondary production as an important metrics of the functional role of these heterotrophic organisms in aquatic environments, once it converts data of density and heterotrophic biomass into a functional measure of the flow of matter and energy. Despite the relevance in estimating the contribution from zooplankton organisms to the ecosystem, are lacking studies on this topic. In the first approach we evaluated the secondary production of rotifer, cladoceran and copepods in two marginal lakes of the Upper Paraná River floodplain, in two hydrological periods. Results showed that zooplankton groups have played different roles in the flow of matter and energy in the floodplain, with dependence on the trophic dynamics and biological characteristics of the groups, besides the temporal and spatial variability of this complex ecosystem. Cyclopoid copepods support better the upper trophic levels given their higher secondary production, however rotifers ease a higher rate of nutrient turnover in the low water period, due to their high turnover. Furthermore, the transfer of matter and energy to upper levels is especially important in the low water period, when the groups? secondary production was greater. The goal of the second approach was to analyze the rotifer community structure and its functional role in marginal lakes of a neotropical floodplain. Results evidenced that environmental conditions in the low water period (higher daily variation) were important in the structure and ecosystem contribution of communities in the lakes. Therefore, it is noteworthy the spatial connectivity between environment in the floodplain, and not only the temporal connectivity, mediated by the flood pulse, as important factor in describing the community and for its functional role in the environment. In summary, ...